Principles of cancer treatment: surgery, radiotherapy, chemotherapy, immunotherapy - Yaeger, Theodore (Henry Stewart Talks, 2009)
Historic principles leading to modern cancer treatments, Specific reviews of surgery, radiotherapy, chemotherapy, hormone therapy and immunotherapy development, Significant developments in present use, Modern concepts using combined modality approaches, Latest technological developments in radiotherapy, Latest developments and implementation of immunotherapy, Discussion of near future events and possibilities
Archived at 2021/02/25